2003
DOI: 10.1007/s10295-002-0007-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential biological indicators for glutaraldehyde and formaldehyde sterilization processes

Abstract: The present study aimed to isolate, select, and evaluate bacterial isolates with potential for use as biological indicators for sterilization with glutaraldehyde and/or formaldehyde. A total of 340 local Bacillus isolates were screened for glutaraldehyde and/or formaldehyde resistance by determination of minimum inhibitory concentrations (MICs), minimum bactericidal concentrations (MBCs), and extinction time and were compared with B. subtilis (var. niger) ATCC 9372, the biological indicator for ethylene oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
4
1
3
Order By: Relevance
“…The glutaraldehyde solution' MIC (0.6 to 1.1%) were greater than that reported by Mazzolla et al (0.3-0.4% for B. subtilis spores) and Serry et al 33 (0.35% for B. atrophaeus ATCC 9372), for 10 6 spores used as the challenge in both studies. However, this result showed that the labeled concentration of glutaraldehyde showed sporicidal efficacy against the spores of the tested strain.…”
Section: Discussioncontrasting
confidence: 61%
“…The glutaraldehyde solution' MIC (0.6 to 1.1%) were greater than that reported by Mazzolla et al (0.3-0.4% for B. subtilis spores) and Serry et al 33 (0.35% for B. atrophaeus ATCC 9372), for 10 6 spores used as the challenge in both studies. However, this result showed that the labeled concentration of glutaraldehyde showed sporicidal efficacy against the spores of the tested strain.…”
Section: Discussioncontrasting
confidence: 61%
“…The selection of potential surrogate species and strains of spore formers used here was based on (i) safety for handling; (ii) availability of type strains from a credible source, such as the ATCC; (iii) ability to yield relatively high titers of spores in a liquid medium from one or more commercial sources; (iv) representation from genera other than Bacillus; and (v) prior history of use as a surrogate/biological indicator (4,11,12,15). Review of the use of Bacillus subtilis and Bacillus atrophaeus strains as surrogates was complicated by the significant changes these taxa have undergone over the years, whereby strains now designated as B. atrophaeus have been referred to in the literature as "B. subtilis var.…”
Section: Hwmentioning
confidence: 99%
“…It would certainly be interesting to determine whether spores in general can be inactivated by using shorter incubation times of formaldehyde, a further pursuit of this objective was not followed during this study. There are other studies that focus on the killing of spores with formaldehyde [29,30]. Although the inactivation of B. atrophaeus spores with formaldehyde followed by an analysis with real-time PCR shows some analytical potential, the massive influence of formaldehyde on DNA is a critical factor that eventually excludes formaldehyde as a suited inactivation reagent for PCR analysis in the here tested concentration range.…”
Section: Discussionmentioning
confidence: 97%
“…There are other studies that focus on the killing of spores with formaldehyde [29,30]. This was achieved with the undiluted sample containing 4.25 Â 10 9 spores/mL and two more log 10 dilutions of the original suspension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation